From Theory to Practice: Exploring the Use of Physical Visualization Objects in Rural Mathematics Classrooms - Ngwabe, Abongile Happy (CV Sinergi Ilmu dan Publikasi, 2026)
Physical visualization objects play a critical role in mathematics education, particularly in rural settings where access to digital resources is limited. This study explores how preservice teachers in rural schools utilize physical visualization objects in mathematics lessons, highlighting their impact on teaching and learning. Guided by Instrumental Genesis Theory and Reflective Practice Theory, the study examines how preservice teachers transform physical objects into instructional tools and adapt their teaching strategies through reflective practice. Adopting a qualitative case study design within an interpretive paradigm, the study involved ten final-year preservice mathematics teachers undertaking teaching practice in rural schools. Data were collected through classroom observations and written reflections and analyzed using thematic analysis to examine preservice teachers’ use of physical visualization objects in mathematics instruction. Findings reveal that physical visualization objects enhance conceptual understanding, learner engagement, and teaching effectiveness. However, challenges such as classroom management, time constraints, and limited access to materials were reported. The study emphasizes the need for structured teacher training to optimize the pedagogical use of physical visualization objects. Future research should investigate the long-term impact of physical visualizations on learner achievement and explore their integration across diverse educational contexts, especially in resource-constrained environments.